Axillary Intra-Aortic Balloon Pump Migration Into the Left Ventricle During Peripheral Venoarterial Extracorporeal Membrane Oxygenation Support. (May 2020) - Alvarez, Chikezie K.; Alvarez Villela, Miguel; Wiley, Jose M.; Taveras, Jose M.; Goldstein, Daniel J.; Sims, Daniel B.; Jorde, Ulrich P.
Abstract : Supplemental Digital Content is available in the text.